INTERGROUP CONFLICTS AND SOCIAL HARMONY: A STUDY OF COMMUNITY INTERACTIONS IN MULTICULTURAL SOCIETIES - Arif Muzayin Shofwan; Amin Zaki; Omar Khan (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
Multicultural societies are increasingly characterized by diversity that brings both opportunities for cooperation and risks of intergroup conflict at the community level. Intergroup tensions and social harmony often coexist, yet their interaction remains insufficiently understood in empirical research. This study aims to examine how community interactions shape intergroup conflicts and social harmony in multicultural societies. A quantitative explanatory design was employed involving community members from diverse ethnic and cultural backgrounds across several multicultural neighborhoods. Data were collected using structured questionnaires measuring intergroup interaction frequency, perceived conflict intensity, and social harmony, complemented by secondary community records. Descriptive statistics, correlation analysis, and multiple regression were used to analyze the data. The results indicate that frequent and meaningful intergroup interactions are significantly associated with lower perceived conflict and higher levels of social harmony. Intergroup interaction emerged as a strong predictor of harmony, while conflict intensity negatively affected harmonious relations. The findings demonstrate that social harmony is actively constructed through everyday interactions rather than achieved by the absence of conflict. Strengthening opportunities for dialogue, shared spaces, and inclusive community engagement can enhance social cohesion. The study concludes that managing diversity through interaction-focused strategies is essential for sustaining peaceful and resilient multicultural communities globally today.